MEMBANGKITKAN MOTIVASI BELAJAR MAHASISWA SAAT PEMBELAJARAN SECARA VIRTUAL PADA MASA PANDEMI COVID 19 - Muhammad Adib Alfarisi; Heriyanto (Bajang Institute, 2021)
People worldwide were shocked by the emergence of the novel Covid-19 virus in early 2020, which first appeared in Wuhan City, the capital of Hubei Province, China. On March 1, 2020, the Minister of Health of the Republic of Indonesia finally reported that the Covid-19 virus had infiltrated Indonesia and infected its citizens. In efforts to overcome and reduce the spread of this dangerous virus, the Indonesian government has required restrictions on activities outside the home. The public has also been obliged to avoid crowds to avoid the spread. In addition, the Indonesian Ministry of Education and Culture also instructs that the learning system must be performed virtually. Online learning has been carried out by utilizing internet technology so that there are no face-to-face meetings between lecturers and students. However, in its implementation, some problems can interfere with the learning process virtually, especially concerning students the lack of learning motivation when carrying out online learning. This research is qualitative research that describes efforts to generate student learning motivation during virtual learning during the Covid-19 pandemic. Motivation to learn is the most crucial factor so that students can receive all learning effectively and efficiently. Therefore, the right stimulants are necessitated in order to arouse their motivation to learn. The research findings indicate what educators should do to increase student learning motivation online is to improve the ability of lecturers, determine appropriate and effective methods, optimize the use of facilities, select appropriate media and conduct periodic evaluations of learning.